ANTIMICROBIAL, ANTIOXIDANT AND ANTICANCER ACTIVITIES OF THAI LOCAL VEGETABLE EXTRACTS: APPLICATION IN A CHINESE-STYLE SAUSAGE - Nanasombat, Suree (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Twenty species of Thai local vegetables were screened for their antioxidant and antimicrobial activities against 19 microbial strains. Methanolic extracts of four plant species, Garcinia cowa, Cassia siamea, Limnophila aromatica and Polygonum ordoratum showing high activities were selected to determine the minimum inhibitory concentration, and evaluate for their anticancer activity against human oral epidermal carcinoma (KB), breast adenocarcinoma (MCF-7) and small cell lung carcinoma (NCI-H187). The sensitive bacteria were Bacillus cereus, Listeria monocytogenes and Staphylococcus aureus. Of all, the extract of P. ordoratum had the highest phenolic content and antioxidant activity with EC50 value of 315.35 microgram extract/ miligram DPPH (2,2-diphenyl-1-picrylhydrazyl), and was moderately active against breast adenocarcinoma (IC50 value of 6.01 microgram/mililiter). Major types of active compounds were identified by HPLC method. Main types of flavonoids found in P. ordoratum were rutin, catechin, quercetin, kaempferol and isorhamnetin. Among all compounds, rutin was found in the highest amount (3.77% w/w dry extract). Then, three formulations of dried vegetable extracts were produced and applied as natural additives in a Chinese-style sausage called Gunchieng. These natural additives (0.1%) were added alone or in combination with sodium lactate (2.5%) in Gunchieng. All natural additives tested were able to retard lipid oxidation during storage at 4 C for 21 days. Treatments with natural additives in combination with sodium lactate resulted in decreasing of microbial counts in Gunchieng by 1.36-2.42 log units after 21-day storage, but the natural additive alone did not cause significant reduction of total microbial counts.